Identity Formation Among Teacher Educators with Visual Impairments in Pakistani Higher Education: A Phenomenological Analysis - Dr. Tahira Batool Bokhari; Dr. Yasira Waqar; Dr. Faisal Anis (Indus Journal of Social Sciences, 2025)
This study employs a phenomenological approach to explore how eight visually impaired teacher-educators in Pakistani higher education institutions shape their identities within institutionally sight-centred environments. Researchers conducted interpretive phenomenological analysis through interviews, journal reflections, and observations to reveal how participants handled the relationship between physical differences and pedagogical competence. This research highlights four main aspects of what it means to exist as a teacher educator with visual impairments: lived body (non-visual engagement with educational spaces), lived relationality (seeking professional recognition within hierarchical structures), lived time (temporal aspects of identity development), and lived space (negotiating accessibility and authority). Participants demonstrate how they surpass stereotypes about people with visual impairment by changing their personal differences into unique teaching practices that question how expert teachers should be seen. The research points out that due to physical absence, teachers rely on different senses, and this changes their traditional beliefs about being skilled in teaching. Blindness is not considered an obstacle to be solved but is thought of as something inspiring and educational. This research provides new concepts for understanding professional identity and suggests ways to create more inclusive policies in Pakistani higher education institutions.